Possibilities of Noncommercial Organizations in the Development of the Sphere of the Services - A. N. Chernyshov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article the role and the place of noncommercial public organizations in the development of the sphere of services is examined. Are designated the basic trends of contemporary social and economic development, which caused an increase in the attention on the social and economic potential NKO. Are revealed the specific features of noncommercial organizations in the totality of the subjects of social and economic system, their comparison with the organizations of the state and commercial sectors of this system is carried out. The results of investigating the economic possibilities NKO are analyzed. Are revealed the problems of state and prospects for development NKO in modern Russia. Is represented the classification of the forms of noncommercial organizations under the conditions of the market economy. Are isolated public health and formation as the priority of the branch of the sphere of the services, directed toward formation and development of human capital as the key resource of social and economic development. Direct and indirect impact NKO on the development of data of branches is determined. Measures for the solution of the problems of the use of potential NKO in the development of the sphere of services are proposed.